O Sofrimento psíquico de mulheres sertanejas usuárias do CAPS de Quixadá - CE - Castelo, Rejane Rodrigues Barbosa (2024)
The Northeastern Sertanejas Women emerge as one of the main protagonists of the current scenario of Psychosocial Care in the Sertão. They bring with them the demand presented in the form of psychic suffering to the Psychosocial Care Centers; Thus, the purpose of this research was to conduct a study on this psychological distress from a gender perspective and to evaluate its impacts on mental health. A reading was carried out in order to know the forms and factors potentially related to Psychic Suffering in women from the countryside; to illustrate a potential strategy of care for women from the countryside who use a CAPS and relate them to the Solidarity Economy in its pillars to think about social inclusion through the work of these women. The methodology used in this research followed a qualitative design, of an exploratory nature, using the triangulation of two methods: action research and content analysis. During the operationalization of the study, the conversation circle strategy was applied, where twelve women who presented similar complaints participated in the group, entitled "Atelier of Meaning". As a result, it was found that the northeastern sertanejo woman has a unique profile, is often conditioned to situations that cause her vulnerabilities such as: gender discrimination in the division of traditional family roles, living with stigma, the absence of autonomy to plan her actions and future and the absence of policies aimed at the subjective way of being in the world. Finally, it is of paramount importance to point out that the legislation related to mental health policies is complied with and implemented, there is a public budget for the allocation of resources that enable the realization of therapeutic projects in an effective way, citizen participation through participatory councils, which allow the women themselves to influence the decisions and monitoring of policies, especially local ones, as well as monitoring and evaluation by inspection bodies in order to assess whether the resources and objectives are obtaining the desired results, and finally the making of adjustments and improvements over time, ensuring the effectiveness of the actions implemented.